Application of Felton and Kuhn's framework for analysing argumentative skills during a role play. - Cruz-Lorite, Isabel María; Evagorou, Maria; Cebrián-Robles, Daniel; Blanco-López, Ángel (My University, 2023)
Argumentation has become important for understanding how people reason and make decisions about socioscientific issues. One challenge of science education is promoting argumentation practices in science classrooms and improving preservice teachers' argumentation skills, which is essential to reinforce their future teaching practices. In this paper, we analyse the preservice primary teachers’ discursive processes when participating in a role play about nuclear power to identify their main limitations in argumentation practice. 28 preservice primary teachers from the University of Málaga participated in this study during the 2018/19 academic year. For data analysis, an adaptation of Felton and Kuhn’s framework was applied. The results show that role play as a teaching strategy has favoured the use of counterarguments and countercritics, although, at the same time, there is also a lack of use of dialogic resources to question the arguments of others.
Keywords: Profesores - Formación profesional; Profesores de ciencias - Formación profesional; Pensamiento; Psicología de la educación; Argumentation; Argumentación; Socio-scientific issues; Problemas sociocientíficos; Juego de rol; Role play